Hydroponic Green Vegetable Cultivation Assistance in Support of SD Negeri 12 Padang Panjang’s Program Towards Achieving Adiwiyata School - Violita, Violita; Holinesti, Rahmi; Sukma, Dina; Mukhlis, Mukhlis; Fronica, Imelda; Putri, Dwi Hilda; Achyar, Afifatul; Handayani, Dezi; Chatri, Moralita; Advinda, Linda; Farma, Siska Alicia; Nabilah, Rezi (Pelita Eksakta, 2025)
Abstract – SD Negeri 12 Padang Panjang is one of the schools that has made efforts to implement the Adiwiyata program. In 2024, the school represented the city of Padang Panjang in the Adiwiyata competition at the West Sumatra provincial level; however, it did not achieve optimal results. For the 2025 Adiwiyata program, SD Negeri 12 has set a target to become the provincial representative of West Sumatra. Based on the evaluation results from 2024, it was found that the assessment indicator for Participatory-Based Environmental Activities needs improvement. One activity that can support this effort is hydroponic cultivation. A hydroponic cultivation training was conducted by 26 fifth-grade students. The training included both theoretical material and hands-on practice in cultivating green vegetables using a hydroponic system. The training was guided by two experts who are competent in the field. This training successfully increased students' knowledge of hydroponic vegetable cultivation. Moreover, over 90% of the participants demonstrated teamwork and developed a greater awareness of environmental care. This outcome is a significant contribution to supporting SD Negeri 12 Padang Panjang Barat’s efforts toward achieving Adiwiyata School status.